Pengaruh Variasi Sudut Guide Vane Terhadap Performa Wind Turbine Darrieus Tipe-H Dengan NACA 0012 Dan NACA 0018 - Sukmana, Bima Mega, NUR AKLIS,ST,M.Eng, Subroto,ST,MT (2016)
To reduce the use of fossil energy sources will be exhausted their availability and to reduce the environmental impact of the use of fossil energy sources hence the need for other energy sources that are environmentally friendly. One of the sources of energy are likely to develop wind. Wind energy can be harnessed using wind turbine. This study aims to determine the influence of guide vane angle variation on the performance of the wind turbine Darrieus type H.Turbine blade design that was tested using NACA 0012 pitch angle of 55° and NACA 0018 pitch angle of 50°.The wind turbine is equipped with additional wind deflector in the form of guide vane.Guide vane angle variation used was 30°, 40°, 50°, 60°, 70°,80°at a wind velocity 4,8 m/s.From the research results obtained, Extra guide vane angle variation on the performance of wind turbine Darrieus type H.When research without loading guide vane angle of 70° to the NACA 0012 and NACA 0018 generate maximum rotation are 78.01 and 77.27 Rpm.When testing with the loading guide vane angle of 70° to the NACA 0012 and NACA 0018 produce power, torque, and efficiency maximum is 0,88 Watt, 1,79 Nm, 5,00% and 0,89 Watt, 1,89 Nm, 5,07%.